2003
DOI: 10.1126/science.1084204
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Goal-Based Motor Selection in the Prefrontal Cortex

Abstract: Choosing an action that leads to a desired goal requires an understanding of the linkages between actions and their outcomes. We investigated neural mechanisms of such goal-based action selection. We trained monkeys on a task in which the relation between visual cues, action types, and reward conditions changed regularly, such that the monkeys selected their actions based on anticipated reward conditions. A significant number of neurons in the medial prefrontal cortex were activated, after cue presentation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
249
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(273 citation statements)
references
References 26 publications
18
249
2
4
Order By: Relevance
“…If response conflict were the only type of conflict to engage the ACC, the data might be consistent with the view that the ACC is itself essentially a motor structure, but perhaps one concerned with selecting among competing responses [19,45]. Although this possibility cannot be ruled out, it is important to note that several studies have provided evidence for ACC activation in the setting of conflict at other levels of processing, including stimulus evaluation [15,41,46] and task representation [20], pointing to a broader monitoring function.…”
Section: Box 1 Conflict Monitoring In the Stroop Tasksupporting
confidence: 59%
See 2 more Smart Citations
“…If response conflict were the only type of conflict to engage the ACC, the data might be consistent with the view that the ACC is itself essentially a motor structure, but perhaps one concerned with selecting among competing responses [19,45]. Although this possibility cannot be ruled out, it is important to note that several studies have provided evidence for ACC activation in the setting of conflict at other levels of processing, including stimulus evaluation [15,41,46] and task representation [20], pointing to a broader monitoring function.…”
Section: Box 1 Conflict Monitoring In the Stroop Tasksupporting
confidence: 59%
“…Importantly, however, the model also suggests that the timing of conflict -and thus of ACC activationshould be qualitatively different in the two cases, tending to precede the overt response on correct trials and to follow it on errors. This predicted difference in the timing of ACC activation has been confirmed in two separate EEG experiments [6,30] eye field, but not in ACC (but see [45]). Although these studies encourage the idea that conflict-related activation lies outside the ACC, it should be noted that they used a version of the go/no-go task, a task which has been clearly shown to engage the ACC in humans [16,18].…”
Section: Localization Of the Conflict Responsementioning
confidence: 68%
See 1 more Smart Citation
“…Category neurons have been identified in other brain regions (25,(37)(38)(39). In an elegant study, Freedman et al (24) showed that deliberate morphing of visual stimuli from one distinct category to another differentially activated prefrontal cortical neurons, which encoded specific categories.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that the dmFC/ACC plays a role in the decision process. Interestingly, this area has been previously implicated in action-based choice: in the context of a human neuroimaging study reporting activity in this area during a task involving choices between different actions compared to a situation involving responses guided by instruction (27) and single neuron recordings have shown that cells in this area were activated only by particular action-reward combinations (47). Another study suggests that this region plays a part in processing the reward information for motor selection (48).…”
Section: Discussionmentioning
confidence: 99%